Nationwide study of spondyloarthritis spectrum and disease characteristics in Egypt - Yasser Emad; Ahmed Elsaman; Hanan El-Saadany; Rawhya R. ElShereef; Yousra Hisham; AlShaymaa Farouk; Gehad G. Elsehrawy; Samar Tharwat; Marwa A. Amer; Osman Hammam; Nevin Hammam; Amany S. ElBahnasawy; et al. (Scientific Reports)
Abstract The aim of this study was to describe the array and disease characteristics of spondyloarthritis (SpA) across Egypt. This work included 1401 SpA patients recruited from 15 specialized Egyptian rheumatology centers representing 20 major cities. The demographic and clinical features, as well as the therapeutic data, were recorded. The mean age of the patients was 37.6 ± 11.4 years, disease duration 8.01 ± 6.7 years, and age at onset 29.9 ± 11 years; 148 (10.6%) were juvenile-onset. There were 813 males and 588 females (M: F 1.4:1). 5.7% were diabetic, 6.1% hypertensive, and 19.3% were smokers. The mean BASDAI was 3.98 ± 1.78, and the BASFI was 4.02 ± 1.77. The human leukocytic antigen (HLA-B27) was positive in 19.8%. Biologic therapy was received by 55.5%, followed by methotrexate (36%) ,steroids (10.8%), and sulfasalazine in 10.7%. In males, the age at onset was significantly lower (p = 0.02), while radiographic axSpA, neuropsychiatric and pulmonary manifestations, HLA-B27 positivity, and receiving biologic therapy were significantly higher (p = 0.02, p < 0.0001, p = 0.03, p < 0.0001, and p < 0.0001). In females, cutaneous manifestations and arthritis were significantly more frequent (p < 0.0001 and p < 0.0001). Those with positive HLA-B27 had a significantly higher frequency of AS (73%) (p = 0.003), male gender (66.2%) (p < 0.0001), longer disease duration (p = 0.001), and were receiving a higher frequency of biologic therapy (89%, p < 0.0001). Radiographic axial SpA was most reported from Assuit (15.9%), nr-axSpA from Cairo (24.5%), peripheral arthritis only from Giza (30.7%), and unclassified from Kafr ElSheikh (33.9%) (p = 0.002). The spectrum of SpA in Egypt is inconsistent across the country. Gender, disease subtype, and HLA-B27 seem to play a key role in the phenotypic presentation.